2020
DOI: 10.1097/qad.0000000000002768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of anticholinergic medication use on brain integrity in persons living with HIV and persons without HIV

Abstract: Objective: This study examined relationships between anticholinergic medication burden and brain integrity in people living with HIV (PLWH) and people without HIV (HIV−). Methods: Neuropsychological performance z-scores (learning, retention, executive function, motor/psychomotor speed, language domains, and global cognition), and neuroimaging measures (brain volumetrics and white matter fractional anisotropy) were analyzed in PLWH (n = 209) and HIV− (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…19 In this setting anticholinergic burden is an emerging issue in ageing HIV-positive participants and may be studied in detail in the setting of clustered PP. 20,21 Although exploratory, the analysis of clusters including ARVs classes showed different patterns for INSTI/NNRTIs (co-administered with the major group of concomitant medications observed in the general analysis) and PIs: the latter seemed to group with drugs used to treat hypertension and cardiovascular disorders. This is an unexpected finding due to the adverse metabolic effect and the potential for cardiovascular toxicity that have been described with certain PIs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…19 In this setting anticholinergic burden is an emerging issue in ageing HIV-positive participants and may be studied in detail in the setting of clustered PP. 20,21 Although exploratory, the analysis of clusters including ARVs classes showed different patterns for INSTI/NNRTIs (co-administered with the major group of concomitant medications observed in the general analysis) and PIs: the latter seemed to group with drugs used to treat hypertension and cardiovascular disorders. This is an unexpected finding due to the adverse metabolic effect and the potential for cardiovascular toxicity that have been described with certain PIs.…”
Section: Discussionmentioning
confidence: 98%
“…Clustering of this drug class with CNS‐active molecules may also prioritize this group of patients for medication review 19 . In this setting anticholinergic burden is an emerging issue in ageing HIV‐positive participants and may be studied in detail in the setting of clustered PP 20,21 …”
Section: Discussionmentioning
confidence: 99%
“…37 Indeed, we have previously shown that some specific medications are associated with increased falls among middle-aged and older PWH. 22 Many NCAE medications are frequently prescribed to PWH, 29,38 who are more also likely to have NCI than their seronegative counterparts. 39,40 NCAE medications may therefore have an even greater effect on falls risk among older PWH who are already at high risk for falls.…”
Section: Introductionmentioning
confidence: 99%
“…Medications with anticholinergic (ACH) activity have been associated with dementia in the elderly general population [ 20 ]. Furthermore, a high ACH burden has been associated with smaller brain volumes and poorer whiter matter structural integrity, and these effects were shown to be more widespread in PWH compared to the general population suggesting that PWH may be more susceptible to ACH medications neurocognitive effects [ 21 ]. Many commonly used medications by PWH have ACH activity (eg, antidepressants, antipsychotics, antihistamines).…”
mentioning
confidence: 99%
“…Many commonly used medications by PWH have ACH activity (eg, antidepressants, antipsychotics, antihistamines). It was recently reported that use of ACH medication is higher in PWH compared to the general population [ 21 ] and that polypharmacy is associated with an increased risk of ACH medication use [ 22 ]. Anticholinergic medication use is a potentially modifiable risk factor that should be evaluated in this high-risk population.…”
mentioning
confidence: 99%